Analysis of Pentagon Fraud Model To detect Financial Statement Fraud (Study on the Industrial ClassificationFinance on the Indonesia Stock Exchange) - Shinta Gem Sari; Alif Akbar Subkhi (Majalah Ilmiah Bijak, 2021)
Fraudulent Practices A is a problem that must be detected at the Earliest time, as an Effort to Protect Company'S assets and maintain the trust of stakeholders. In Financial Service Companies, Especial Banking Companies, Fraud is Susceptible to Occur. The Company's Needs An Approach to Detect Fraud, Especially Financial Statement Fraud. The Pentagon Fraud Model is an approach to detect financial statement fraud. Pentagon Fraud Consists of Four Elements: Pressure (Financial Targets, Financial Stability, External Pressure, and Institutional Ownership); Opportunity (Ineffective Monitoring and Quality of External Auditor); Rationality (auditor change); Capability (Change of Directors); AndroRegance (Director's Appearance). The Population of Thist Study is Companies in the Financial Industry Classification Listed on the Indonesian Stock Exchange by Determining The Sample Using Purposive Sampling Methods. THIS STUDY USING FOUR Years Period from 2016-2019 and Optains 29 companies Selected for Data Testing. Hypothesis testing uses multiple regression analysis. The Results of Analysis Show Thrang Financial Targets (Inspective Indicators), and director of the views (Arrogance Indicator) Affect Financial Statement Fraud. Meanwhile, Financial Stability, External Pressure, Institutional Ownerships US Indicators of Pressure US US The Quality of External Auditor, Auditor Change, and Change of Directors do not AffectFinancial Statement Fraud.